2009
DOI: 10.1542/peds.2008-2698
|View full text |Cite
|
Sign up to set email alerts
|

Acute Illness Care Patterns Change With Use of Telemedicine

Abstract: The Health-e-Access telemedicine model holds potential to reduce health care costs, mostly through replacement of ED visits for nonemergency problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 17 publications
0
70
0
1
Order By: Relevance
“…Telemedicine has also successfully reduced the costs of healthcare and time related to physician travel in addition to reducing the time and out of pocket expenses for patients and families who may need to travel from remote or hard-to-reach locations for their care (49)(50)(51). In many cases, the use of telemedicine in the ambulatory setting has reduced the need for office visits and hospitalizations, mitigated the use of emergency department for nonemergency problems, increased parent satisfaction, and enhanced effective population health management (52). Evolving reimbursement models that emphasize value-based instead of volume-based care have the potential to further contribute to the adoption of telemedicine in the ambulatory setting.…”
Section: More Efficient Use Of Tertiary Care Resourcesmentioning
confidence: 99%
“…Telemedicine has also successfully reduced the costs of healthcare and time related to physician travel in addition to reducing the time and out of pocket expenses for patients and families who may need to travel from remote or hard-to-reach locations for their care (49)(50)(51). In many cases, the use of telemedicine in the ambulatory setting has reduced the need for office visits and hospitalizations, mitigated the use of emergency department for nonemergency problems, increased parent satisfaction, and enhanced effective population health management (52). Evolving reimbursement models that emphasize value-based instead of volume-based care have the potential to further contribute to the adoption of telemedicine in the ambulatory setting.…”
Section: More Efficient Use Of Tertiary Care Resourcesmentioning
confidence: 99%
“…Because only one SLC-based primary Full code 98 (21,(17)(18)(19)(20)(21)(22)(23)(24) 153 (20,(17)(18)(19)(20)(21)(22) *Care status categories not mutually exclusive.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies of telemedicine for acute illnesses in children in schools and daycare facilities have found it to be highly feasible, acceptable, effective, and cost-effective. [15][16][17][18] Preliminary studies involving nursing home residents and other adult populations have also demonstrated the feasibility and acceptability of telemedicine, including its use for acute illness, and these studies have revealed enhancements in clinical care. [19][20][21][22][23][24][25][26][27][28][29] Thus, telemedicine may have significant value in the SLC setting; however, to our knowledge, no studies have evaluated this potential.…”
mentioning
confidence: 99%
“…Previous studies have evaluated the feasibility of telemedicine in assessing and treating ill children. [9][10][11] Few studies have formally evaluated how reliable telemedicine is; that is, whether data presented with telemedicine are similar to observations made at the bedside. 12 In addition, the evaluation of a seriously ill child poses a challenge for telemedicine in that telemedicine is primarily visual in its application and has limited ability to perform nonvisual components of the physical examination (eg, palpation, percussion).…”
mentioning
confidence: 99%